2019
DOI: 10.1016/j.scitotenv.2019.06.362
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclides in surface waters around the damaged Fukushima Daiichi NPP one month after the accident: Evidence of significant tritium release into the environment

Abstract: Following the Fukushima nuclear accident (2011), radionuclides mostly of volatile elements (e.g., 131 I, 134,137 Cs, 132 Te) have been investigated frequently for their presence in the atmosphere, pedosphere, biosphere, and the Pacific Ocean. Smaller releases of radionuclides with intermediate volatility, (e.g., 90 Sr), have been reported for soil. However, few reports have been published which targeted the contamination of surface (fresh) waters in Japan soon after the accident. In the present study, 10 sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Querfeld et al 14 reported that 10 surface water samples (collected on April 10, 2011) have been screened for their radionuclide content ( 3 H, 90 Sr, 129 I, 134 Cs, and 137 Cs). The highest levels, 184 ± 2 Bq/L, ever reported in scientific literature after Fukushima were found in a puddle water sample from close to the Fukushima Daiichi Nuclear Power Plant (FNPP1).…”
Section: Discussionmentioning
confidence: 99%
“…Querfeld et al 14 reported that 10 surface water samples (collected on April 10, 2011) have been screened for their radionuclide content ( 3 H, 90 Sr, 129 I, 134 Cs, and 137 Cs). The highest levels, 184 ± 2 Bq/L, ever reported in scientific literature after Fukushima were found in a puddle water sample from close to the Fukushima Daiichi Nuclear Power Plant (FNPP1).…”
Section: Discussionmentioning
confidence: 99%
“…Aerosols acquire charge due to both beta decay and alpha decay, and it is not only the aerosols but also the surrounding air that becomes ionized (Gensdarmes et al, 2001). Radioactive aerosols may contain a mixture of radionuclides (Cuddihy et al, 1989;Querfeld et al, 2019), and this will influence the charge; many other factors also contribute, including the specific radionuclide activity, the aerosol concentration and particle size, and the asymmetry parameter of the ion flux. A radioactive aerosol can be partially neutralized by ion pairs produced in the surrounding region from the decay of other radioactive aerosols in its vicinity, but this may change when there is dilution with air that is less heavily ionized; in this case, the radioactive aerosol concentration will decrease, and the ability of radioactive decaygenerated ion pairs to interact with neighboring aerosols will decrease.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…1 This exposure may stem from major radiation crises, such as the Fukushima nuclear plant, which is still an ongoing disaster, continuously leaking radioactive materials and contaminating freshwater, sea water, air, and soil. [2][3][4] In addition to these rare but catastrophic accidents, people are also frequently or constantly exposed to the everyday irradiation from these types of sources, which include cosmic rays, naturally abundant radioisotopes, and the X-rays from hospitals. 5 People are worried about radioactivity, because they can be directly affected by it and the devastating effects that can take place many years later or even in the next generation.…”
Section: Introductionmentioning
confidence: 99%